From Coal Pits to Tar Sands: Labour Migration Between an Atlantic Canadian Region and the Athabasca Oil Sands - Ferguson, Nelson (Just Labour, 2011)
The ongoing developments of the Northern Albertan Athabasca Oil Sands include exceptionally labour intensive processes, while securing labour for this industry has been a perpetual challenge. The industry has relied on temporary and transitory labour since its inception, with a great deal of mobile workers originating from Atlantic Canada. Based on ethnographic research, this paper examines the dynamics of an emerging route of migration between the former coal-mining region of Industrial Cape Breton, Nova Scotia and the sites of the Oil Sands industry. Processes of migration have had profound social and economic impacts on the communities of Industrial Cape Breton, while such mobile workers find themselves in a form of work organization which is increasingly precarious and contingent.